Sulphonylurea sensitivity and enriched expression implicate inward rectifier K+ channels in Drosophila melanogaster renal function. - Evans, J.M.; Allan, A.K.; Davies, S.A.; Dow, J.A.T. (Journal of Experimental Biology, 2005)
Insect Malpighian (renal) tubules are capable of transporting fluid at remarkable rates. Secondary active transport of potassium at the apical surface of the principal cell must be matched by a high-capacity basolateral potassium entry route. A recent microarray analysis of Drosophila tubule identified three extremely abundant and enriched K(+) channel genes encoding the three inward rectifier channels of Drosophila: ir, irk2 and irk3. Enriched expression of inward rectifier channels in tubule was verified by quantitative RT-PCR, and all three IRKs localised to principal cells of the main segment (and ir and irk3 to the lower tubule) by in situ hybridisation, suggesting roles both in primary secretion and reabsorption. A new splice form of irk2 was also identified. The role of inward rectifiers in fluid secretion was assessed with a panel of selective inhibitors of inward rectifier channels, the antidiabetic sulphonylureas. All completely inhibited fluid secretion, with IC(50)s of 0.78 mmol l(-1) for glibenclamide and approximately 5 mmol l(-1) for tolbutamide, 0.01 mmol l(-1) for minoxidil and 0.1 mmol l(-1) for diazoxide. This pharmacology is consistent with a lower-affinity class of inward rectifier channel that does not form an obligate multimer with the sulphonylurea receptor (SUR), although effects on non-IRK targets cannot be excluded. Glibenclamide inhibited fluid secretion similarly to basolateral K(+)-free saline. Radiolabelled glibenclamide is both potently transported and metabolised by tubule. Furthermore, glibenclamide is capable of blocking transport of the organic dye amaranth (azorubin S), at concentrations of glibenclamide much lower than required to impact on fluid secretion. Glibenclamide thus interacts with tubule in three separate ways; as a potent inhibitor of fluid secretion, as an inhibitor (possibly competitive) of an organic solute transporter and as a substrate for excretion and metabolism.